Transition Metal Based Biologically Active Compounds As Selective Antifungal Agents - S.SOBHA; N.RAMAN (International Journal of Pharma and Bio Sciences, 2012)
The in vitro antifungal activities of few novel 4-aminoantipyrine derived Schiff bases and their metal complexes were tested against fungi such as Aspergillus niger, Fusarium solani, Culvularia lunata, Rhizoctonia bataicola and Candida albicans. All the metal complexes showed stronger antifungal activities than the free ligands. The synthesized compounds were subjected to molecular docking studies for the inhibition of the enzyme glucosamine-6-phosphate synthase which is a new target for antifungals